Studi Literatur: Evolusi Konsep Literasi Sains dalam Kurikulum Indonesia dari KTSP Hingga Kurikulum Merdeka - Rina Hidayati Pratiwi; Sihite, Julius; Ani Hoerunisa; Yudha Ningsih; Almaida Garudea Putri (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
The development of the education curriculum in Indonesia reflects a paradigm shift in strengthening scientific literacy, which plays an important role in shaping critical thinking patterns and student analysis to face the challenges of the 21st century. This study aims to examine the development of the concept of scientific literacy in the Indonesian national curriculum policy from the era of the School Level Curriculum (KTSP), the 2013 Curriculum, to the Merdeka Curriculum. The study was conducted through a literature study method on 20 relevant scientific articles published in the period 2013 to 2025. The results of the study show that scientific literacy in the KTSP is still implicit, limited to contextual learning approaches and direct experience. In the 2013 Curriculum, strengthening scientific literacy began to be realized through a scientific approach that encouraged students to develop critical thinking skills, understand scientific concepts, and carry out scientific processes systematically. Further transformation is seen in the Merdeka Curriculum, where scientific literacy is not only focused on cognitive aspects, but is also linked to character values ​​and contextual problem solving through strengthening the Pancasila Student Profile and project-based learning. In general, this study concludes that there is a paradigm shift from knowledge-oriented science literacy to holistic and applied science literacy. This finding emphasizes the importance of continuity between policy curriculum, teacher professional development, and implementation of strategies in the field to optimize students' achievement of science literacy.